Unveiling the effect of Nb and Zr additions on microstructure and properties of β Ti-25Ta alloys for biomedical applications - Kuroda, Pedro Akira Bazaglia; dos Santos, Rafael Formenton Macedo; Grandini, Carlos Roberto [UNESP]; Afonso, Conrado Ramos Moreira (Elsevier, 2024)
This study aims to analyze the influence of niobium and zirconium in the structure, microstructure, and mechanical properties of quaternary Ti-25Ta-Zr-Nb alloys system: Ti-25Ta, Ti-25Ta-10Zr-15Nb, and Ti-25Ta-20Zr-30Nb (wt%). The structural and microstructural analyses were performed using X-ray diffraction, as well as optical, scanning and transmission electron microscopy. Rietveld method was used for calculating the volume fractions of crystalline phases and values of β lattice parameters. Williamson-Hall's equation calculated the micro-strain and average size of the β-phase crystallite. The mechanical properties were analyzed by microhardness and Young's modulus measurements. The results show that the different heat treatments influence the structure of the materials and the mechanical properties: Rapid cooling treatments induced the formation of α″ and β for Ti-25Ta-10Zr-15Nb (TTZN1), while the treatments with slow cooling induced the formation of α phases. The Ti-25Ta-20Zr-30Nb (TTZN2) alloy is a stable β, so heat treatments could not change the crystalline structure. To Ti-25Ta alloy, in all study conditions, the alloy has α + α″ phases. Regarding the lattice parameters, adding niobium to the alloys increased the lattice parameter of the β phase. Concerning the β phase micro-strain and average crystal size, the heat treatments increased the average size and micro-strain due to the crystallization of the crystals. β-Ti alloys in the solubilized heat treatment condition, followed by rapid cooling, showed better mechanical biocompatibility results due to the low elastic modulus, highlighting the metastable β Ti-25Ta-10Zr-15Nb alloy, which showed a low elastic modulus of 50 GPa.
Keywords: Biomaterial; Characterization; Elastic modulus; Ti alloys